2016
DOI: 10.1242/dev.134817
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in cell motility reveals the dynamic nature of the formation of zebrafish taste sensory organs

Abstract: Taste buds are sensory organs in jawed vertebrates, composed of distinct cell types that detect and transduce specific taste qualities. Taste bud cells differentiate from oropharyngeal epithelial progenitors, which are localized mainly in proximity to the forming organs. Despite recent progress in elucidating the molecular interactions required for taste bud cell development and function, the cell behavior underlying the organ assembly is poorly defined. Here, we used time-lapse imaging to observe the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…Laser ablation of Type III cells has further shown that this cell type is required for the maintenance of Fgf8a-expressing cells by the taste bud. However, none of the motility modes of Type II cells relies on the Ascl1/5-HT/Type III cell, and taste buds do form in Ascl1a −/− larvae (Soulika et al, 2016), suggesting that different molecular mechanisms regulate the motility and assembly of Type II cells into taste buds.…”
Section: Taste Bud Formation: Getting Together In Many Waysmentioning
confidence: 99%
See 4 more Smart Citations
“…Laser ablation of Type III cells has further shown that this cell type is required for the maintenance of Fgf8a-expressing cells by the taste bud. However, none of the motility modes of Type II cells relies on the Ascl1/5-HT/Type III cell, and taste buds do form in Ascl1a −/− larvae (Soulika et al, 2016), suggesting that different molecular mechanisms regulate the motility and assembly of Type II cells into taste buds.…”
Section: Taste Bud Formation: Getting Together In Many Waysmentioning
confidence: 99%
“…The cell has directed motility, i.e. it migrates, and this occurs within the epithelium of origin (intraepithelially) (Kuo and Krasnow, 2015;Noguchi et al, 2015;Soulika et al, 2016). It is currently unclear to what extent a slithering cell shares similar molecular characteristics with cohorts of cells undergoing EMT (see below).…”
Section: Box 2 Types Of Epithelial Cell Displacement Occurring Durinmentioning
confidence: 99%
See 3 more Smart Citations